THE EFFECT OF ADDITIONAL DOSES OF CURCUMA FLOUR (Curcuma xanthorrhiza Roxb) IN FEED ON THE GROWTH OF GOURAMY (Osphronemus gouramy) FRY - Wardani, Rizka Maulina; Herman, Roffi Grandiosa; Haetami, Kiki; Iskandar, Iskandar (AQUASAINS, 2024)
The purpose of this study was to determine the optimum content of the addition of curcuma flour with different doses to the feed on the growth of gourami fry (Osphronemus gouramy). The method used in this study was a completely randomized design (CRD) experimental method, which consisted of 5 treatments with 3 replications. The treatment used was treatment (A) without giving curcuma flour (control), (B) giving curcuma flour at 2.5%/kg feed, (C) giving curcuma flour at 5%/kg feed, (D) giving curcuma flour ginger at 7.5%/kg feed, (E) giving curcuma flour at 10%/kg feed. The results of analysis of variance (Anova) showed that the addition of the flour at different doses had a significant effect (P<0.05) on the growth of gouramy fish fry. The results showed that the addition of curcuma flour at 7.5%/kg of feed gave the best results with the highest absolute weight growth of 15.11 ± 0,42 g, the highest absolute length growth of 3.92 ± 0,42 cm, the feed conversion ratio of 1.95 ± 0.11, and survival of 100%. Keywords: Gouramy fish, curcuma flour, growth, feed.